Effects on Synchronization and Reproductive Efficiency of Delaying the Removal of the Intravaginal Progesterone Device by 24 h in the 5d Co-Synch Protocol in Heifers - Fernandez-Novo, Aitor (Animals (Basel), 2021)
SIMPLE SUMMARY: Reproductive biotechnologies in beef farms are key issues, such as artificial insemination, fixed-time artificial insemination (FTAI), embryo transfer, and ovum pick up, among others. Artificial insemination takes the first place with these available tools. Thus, science keeps improving hormonal treatments and procedures to optimize pregnancies after insemination. A synchronization protocol commonly used in beef heifers is the 5d Co-synch protocol, which fits better in terms of ovarian synchronization and resulting conception rate. We propose a modification of this protocol, which consists of delaying by 24 h the removal of the intravaginal progesterone device, to decrease the percentage of heifers showing estrus before the date of FTAI. Moreover, this modification will make easier the workload when inseminating herds with heifers and cows at the same time. Based on our results, the protocol 5d Co-synch with the delayed removal of the intravaginal progesterone device fits as well as the original protocol in terms of synchronization and conception rate. Therefore, it can be implemented in the heifers of beef cattle commercial farms. ABSTRACT: In beef herds, increasing animal welfare, improving reproductive performance and easing animal management are key goals in farm economics. We explored whether delaying the removal of the intravaginal progesterone device by 24 h in heifers synchronized with a 5d Co-synch 72-h protocol could improve reproductive efficiency of fixed-time artificial insemination (FTAI). In experiment 1, we examined the total synchronization rate (TSR) in cycling Holstein heifers. Heifers (13.4 ± 0.69 mo.) were randomly assigned to the standard 5d Co-synch 56-h protocol (5dCo56; n = 10), 5d Co-synch 72-h (5dCo72; n = 17), or the modified 5d Co-synch 72-h protocol, in which removal of the progesterone device was delayed by 24 h (6dCo48; n = 19). In experiment 2, 309 cycling beef heifers on 18 commercial farms were subjected to the 5d Co-synch 72-h or 6-d Co-synch 48-h protocol and conception rate (CR) studied. In experiment 1, the three protocols led no differences on TSRs of 80.0% (5dCo56), 88.2% (5dCo72), and 89.5% (6dCo48). In experiment 2, the CR from the beef heifers, observed during two consecutive reproductive seasons did not differ: 59.7% for 5dCo72 and 62.0% for 6dCo48 (p = 0.907). Therefore, delaying removal by 24 h provides satisfactory results without reducing reproductive efficiency of heifers.